Efficacy, mutagenicity and toxicity of trichosetin as a new antibiotic for poultry - Marfori, Eufroncio C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
Trichosetin is a new antibiotic produced from the dual culture of Catharanthus roseus callus and Trichoderma harzianum. Experiments were conducted to determine its efficacy and safety as a therapeutic agent for poultry. Antimicrobial assay showed that this antibiotic was inhibitory to a multidrug-resistant strain of Staphylococcus sp. It also exhibited moderate activity against Pasteurella multocida. Toxicity assay showed that it was not toxic to chicken when administered orally at 50 mg kg-1 body weight daily for 1 wk. Mutagenicity assay revealed that it was not mutagenic. These results suggest that trichosetin can be developed as a therapeutic agent for poultry.